Optimum layout design of onshore wind farms considering stochastic loading. (October 2015) - Kallioras, Nikos Ath.; Lagaros, Nikos D.; Karlaftis, Matthew G.; Pachy, Paraskevi
Highlights: Wind load simulation using stochastic fields. Two formulations for the problem of optimum layout design of onshore wind farms. Consideration of the wake effect along various wind directions. Discrete variant the harmony search algorithm. Abstract: Renewable energy technologies are developing rapidly, while in the last decade great interest is encountered in the use of wind energy, especially due to the energy crisis and serious environmental problems appeared from the use of fossil fuels and therefore a large number of wind farms have been installed around the world. On the other hand the ability of nature inspired algorithms to efficiently handle combinatorial optimization problems was proved by their successful implementation in many fields of engineering sciences. In this study, a new problem formulation for the optimum layout design of onshore wind farms is presented, where the wind load is implemented using stochastic fields. For this purpose, a metaheuristic search algorithm based on a discrete variant of the harmony search method is used for solving the problem at hand. The farm layout problem is by nature a constrained optimization problem, and the contribution of the wake effects is significant; therefore, in two formulations presented in this study the influence of wind direction is also taken into account and compared with the scenario that the wake effect is ignored. The results of this study proved the applicability of the proposed formulations and the efficiency of combining metaheuristic optimization with stochastic wind loading for dealing with the problem of optimal layout design of wind farms.